Comparison of Coalition and Single-Party Governments in Terms of Sustainable Politics: The Interaction of Party and Election Systems Between 1950-2015 - Alptekin, Gökhan (Journal of Applied And Theoretical Social Sciences, 2021)
Turkish political life has been assessed as having gained considerable experience in a short period of time, although it is constantly referred to instability and economic fluctuations. Having tried many party systems and electoral systems, having a political life enriched by single-party governments and multiple instances of coalition government periods, is in fact very valuable for the country's interests. At this point, the various interventions of the pressure groups have also been witnessed. Almost in every decade, military coups or interventions have prevented democracy from developing on the political horizon and have caused the failure of the mentioned wealth to be fully taken. It would not be wrong to say that the multi party political life in Turkey started from 1950. In this context, it has been determined that an expert of almost seventy years does not have enough scientific articles to be written in subject. In this study, the elections between 1950 and 2015 were considered and the political and economic stability of the single party and coalition governments established was investigated. From the results obtained, a definition of sustainable politics has been tried to be made. In this sense, based on economy definitions such as growth, inflation, and unemployment have sought to demonstrate the importance of sustainability through democracy, participation culture, pluralism and political morality.